Supporting every child : a course book for foundation degrees in teaching and supporting learning - Walton, Anita; Goddard, Gillian (Exeter : Learning Matters, 2009)
This is a course book for foundation degree students who are support staff working predominantly in a range of educational settings. It focuses on professional, academic and vocational issues that are common to support workers across the school sectors and provides relevant guidance that responds to recent workforce developments.
Keywords: Teachers' assistants -- Great Britain; EDUCATION -- Teaching Methods & Materials -- General